2020
DOI: 10.24251/hicss.2020.171
|View full text |Cite
|
Sign up to set email alerts
|

I Spy with my Little Sensor Eye - Effect of Data-Tracking and Convenience on the Intention to Use Smart Technology.

Abstract: The increasing number of smart objects in private households leads to a profound invasion of privacy. Based on privacy calculus theory, we assume that many users accept tracking in exchange for full functioning and convenience. However, privacy calculus has not yet been tested in an area where privacy protection is a binary decision: to either use a product or not. Therefore, we examined the effect of convenience and tracking on the intention to use a smart device in a 2 x 2 betweensubjects online experiment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…These results are contrary to the basic assumption of the privacy calculus and contradict the findings of a recent study that also collected behavioral data (Dienlin et al, 2019). Although plenty of studies have found support for the basic assumption of the privacy calculus (e.g., Bol et al, 2018;Dienlin & Metzger, 2016;Krasnova et al, 2009;Princi & Krämer, 2020), the approach is not without criticism (Knijnenburg et al, 2017). The vast majority of pri-vacy calculus studies focused on intentions rather than on behavioral data (with the exception of the study by Dienlin et al, 2019).…”
Section: Privacy Decision-makingcontrasting
confidence: 67%
See 1 more Smart Citation
“…These results are contrary to the basic assumption of the privacy calculus and contradict the findings of a recent study that also collected behavioral data (Dienlin et al, 2019). Although plenty of studies have found support for the basic assumption of the privacy calculus (e.g., Bol et al, 2018;Dienlin & Metzger, 2016;Krasnova et al, 2009;Princi & Krämer, 2020), the approach is not without criticism (Knijnenburg et al, 2017). The vast majority of pri-vacy calculus studies focused on intentions rather than on behavioral data (with the exception of the study by Dienlin et al, 2019).…”
Section: Privacy Decision-makingcontrasting
confidence: 67%
“…If the perception of costs outweighs the perception of benefits, self-disclosure is reduced or unlikely. Several studies have found empirical support for the impact of privacy costs and benefits on self-disclosure intentions or technology adoption in a variety of different settings and contexts (e.g., Bol et al, 2018;Dienlin & Metzger, 2016;Krasnova, Kolesnikova, & Guenther, 2009;Princi & Krämer, 2020). These studies examined various kinds of anticipated privacy costs, among them privacy concerns (e.g., Dienlin & Metzger, 2016) or privacy risk beliefs (e.g., Bol et al, 2018).…”
Section: Privacy Calculusmentioning
confidence: 99%
“…The privacy calculus (Culnan & Armstrong, 1999) assumes people to weigh the perceived privacy costs and perceived benefits before they decide to disclose personal information (Dienlin & Metzger, 2016), install an app (Eling et al, 2013) or adopt new technology (Princi & Krämer, 2020). For instance, perceived privacy costs (e.g., privacy threats) have been found to negatively affect online self-disclosure (Bol et al, 2018) or the likelihood to install an app (Eling et al, 2013).…”
Section: Privacy Calculusmentioning
confidence: 99%
“…Several studies have found that the anticipation of social benefits increases the likelihood of information disclosure on social networking sites (SNSs; Krasnova et al, 2010), or that the perception of convenience increases likelihood of smart technology adoption (Zheng et al, 2018). Generally, benefit perceptions are frequently found to be the driving factor for self-disclosure or technology adoption (e.g., Dienlin & Metzger, 2016;Krasnova et al, 2014;Princi & Krämer, 2020). This can be explained by the gratification hypothesis that assumes the expected benefits to outweigh the perceived risks, for instance, because people overrate the gratifications or because they are unaware of the privacy threats (Trepte et al, 2015).…”
Section: The Influence Of Benefitsmentioning
confidence: 99%